Interpretação da resistividade aparente do solo e estratificação com arranjo de Schlumberger - Viana , Fernando Moreira (2016)
This work proposes a methodology for interpretation of soil resistivity measurements obtained using the arrangement of four electrodesWenner, Schlumberger and Schlumberger-Palmer. Displays can be compared apparent resistivity curves when the quantity used in the abscissa is the effective depth of investigation. This magnitude that depends on the geometry of the electrodes, namely the positioning of both current electrodes and the potential electrodes. The work also features in an innovative way, an algorithm for soil stratification from resistivity measurements obtained with the Schlumberger arrangement. The same is based on the method of complex images and propose a finite number of complex exponentials to represent the kernel function. Several simulations are performed, proving the efficiency and effectiveness of the proposed algorithm.